Monofilament Gillnet Selectivity for Hampala Barb (Hampala macrolepidota) Management at Ir. H. Djuanda Reservoir-West Java - Andri Warsa; LIsmining Pujiyani Astuti (Journal Omni-Akuatika, 2019)
Ir. H. Djuanda Reservoir have high fishes biodiversity and one of them is Hampala barb (Hampala macrolepidota) and it’s economical species. Hampala barb is one of dominant species was captured at Ir. H. Djuanda Reservoir but was experience decreasing of population by overfishing. The objective of this research were to known gillnet selectivity and length at first mature for hampala barb (Hampala macrolepidota) at Ir. H. Djuanda Reservoir. The information will be used as base determination of gillnet mesh size and legal size for sustainability fisheries management. The research was done at February-September 2017 with experimental fishing used gillnet with mesh size between 1.0-3.0 inch with intervals 0.5 inch. Total length hampala barb with highest captured probability for gillnet with mesh size 1.0; 1.5; 2.0; 2.5 and 3.0 inch were 11.0; 17.0; 22.5; 28,0 and 33.5 cm respectively. Length at first mature of hampala barb for female and male were 14.2 and 13.8 cm respectively. Based on the information, the minimum total length for exploitation was 19 cm using gillnet with mesh size > 2.0 inch.